Case study -- beef industry in China: food safety in food security and food trade - Brown, Colin G.; Waldron, Scott A. (International Food Policy Research Institute, 2003)
The beef industry provides a window on food safety issues in China’s rapidly developing economy. This industry provides particularly useful insights because the government has targeted it for development and because it is dominated by household slaughtering and wet markets, making food safety concerns pervasive.